Different Methods of Evaluating Student Translations: The Question of Validity - Waddington, Christopher (Meta, 2001)
Abstract This article examines the criterion-related validity of the results obtained by the application of four different methods of assessment to the correction of a second-year exam of translation into the foreign language (Spanish-English) done by 64 university students. These four methods are based on types currently used by university teachers, and the validation study is based on 17 external criteria taken from six different sources. In spite of this variety, a factor analysis reveals the presence of one main factor which is clearly identifiable as Translation Competence . The hypotheses regarding differences between the validity of the methods are verified as null, since all the systems, whether based on error analysis or a holistic approach, prove to correlate significantly with this main factor.